(untitled) (Global Journal of Science Frontier Research, 2016)
A class of entire bicomplex sequences denoted by B, studied by Srivastava & Srivastava in 2007 is studied and is shown to be a bicomplex module. The subclasses of this class, studied by Wagh in 2008, are also shown to be bicomplex modules. Further they have been shown to form module structure over the class B.